Anthropometric Study of Cephalic and Facial Indices among Central Indian Population (Indian Internet Journal of Forensic Medicine and Toxicology, 2020)
Facial and Cephalic indices are the type of somatometric measurements in physical anthropology. These kinds of indices established the personal identity of a person on the basis of its sex and ethnic group. The aim of the present study is to establish baseline data of cephalic index and facial index of central Indian population (Indore Region) and comparison of present study with previous studies. These data will be helpful for forensic anthropologists, anatomists and related fields. The mean value of cephalic index and facial index found in the study were 70.36, 101.64 the basis respectively in male and 68.72, 100.34 respectively in female. The major head type found in the study was dolichocephalic and hyper leptoprosopic type of face.
Keywords: Cephalic index; Dolichocephalic; Facial index; Hyper leptoprosopic; Physical anthropology